Le fantastique canadien actuel : bref aperçu - Boussad Berrichi (Asociación de Francesistas de la Universidad Española (AFUE), 2016)
In this article we will present the contemporary francophone fantastic in Canada and its relation to the past tradition. To start with, we will make a short overview of the different genres of the fantastic in order to understand the concrete realizations of those genres in the francophone literatures of Canada (in plural). Second, we will summarize the evolution of the francophone fantastic until nowadays by studying at the same time some aspects of the fantastic through different times and some common themes. Finally, we will deal with some essential works (such as those written by Yann Martel, Hédi Bouraoui, etc.) and the tendencies of those fantastic literatures in Canada.